KEANEKARAGAMAN JENIS PAKU-PAKUAN (Pteridophyta) EPIFIT DI LINGKUNGAN ARBORETUM SYLVA UNIVERSITAS TANJUNGPURA PONTIANAK - Wahyudi, Eko; Prayogo, Harri; Tavita, Gusti Eva (Universitas Tanjungpura, 2018)
The purpose of this study was to examine and record the diversity of epiphytic ferns in the environment of the Sylva Arboretum of Tanjungpura University Pontianak. The benefit of this research is provide information on the diversity and benefits of epiphytic ferns for human life. Sylva Arboretum University of Tanjungpura has a variety of plant diversity that lives in it, especially ferns that need to be studied to provide information that is very important to know. This research began on May 19 to June 9, 2017 with the survey method with the line technic (long as of 60 m x 5 m) each line didived into 6 plots. Based on the results this study found 3 species of epiphytic ferns from the polypocidae family. Species of ferns that found are bird nest nails (Asplenium nidus), dragon scales (Drymoglossum piloselloides) and closed nails (Davilia denticulata).Keyword : Arboretum Sylva, Diversity, Epipihytes, Pteridophyta.